Immunohistochemical analysis of the D-type cyclin-dependent kinases Cdk4 and Cdk6, using a series of monoclonal antibodies - Lukas, C; Jensen, S K; Bártková, Jiřina; Lukáš, Jiří; Bártek, Jiří (Hybridoma, 1999)
Cellular signal transduction cascades triggered by mitogenic or antiproliferative cues eventually converge on a biochemical mechanism centered around the retinoblastoma tumor suppressor (pRb), the so-called RB pathway that governs G1-phase progression and guards the commitment to enter S phase. pRb, together with its immediate upstream regulators, the D-type cyclins, their partner cyclin-dependent kinases Cdk4 and Cdk6, and the Cdk inhibitors, form a functional unit that is involved in major decisions about cellular fate, and whose components, including the proto-oncogenic cyclin D-dependent kinases, are commonly deregulated in many types of cancer. We report here the production and characterization of a series of 12 monoclonal antibodies (MAbs) that specifically recognize either Cdk4 or Cdk6. These antibodies are proving to be invaluable molecular probes for defining abundance, subcellular localization, binding partners, and ultimately the function(s) of these cell cycle-regulatory kinases. Localization of the target epitopes was mapped by peptide enzyme-linked immunoadsorbent assay (ELISA), and two antibodies recognizing sequences adjacent to N-terminus of Cdk4 can discriminate between the wild-type protein and the oncogenic, melanoma-associated R24C mutant of this kinase. Individual antibodies of our panel recognize distinct pools of Cdk4/6, a feature reflected by their differential applicability in immunoblotting, immunoprecipitation, kinase assays, and immunostaining including immunohistochemistry on archival paraffin-embedded tissue sections. Collectively, the antibodies described in this study provide the means for immunochemical analyses of the cyclin D-dependent kinases in human and animal cells, and represent useful molecular tools that should help better understand the biological roles of Cdk4 and Cdk6 in normal cell-cycle control, and their oncogenic activity in tumor cells.
Keywords: Cyclin-Dependent Kinase 4; nádory; cyklin-dependentní kinasa 4; DNA Primers; mapování epitopu; hybridomy; buněčné linie; Humans; Mutation; Cell Line; DNA primery; Mice; zvířata; monoklonální protilátky; Rats; cyklin-dependentní kinasa 6; Antibodies, Monoclonal; imunohistochemie; Immunohistochemistry; sekvence nukleotidů; protoonkogenní proteiny; Immunochemistry; Proto-Oncogene Proteins; Cyclin-Dependent Kinase 6; Cyclin-Dependent Kinases; Retinoblastoma Protein; Epitope Mapping; retinoblastomový protein; krysa rodu Rattus; myši; protein-serin-threoninkinasy; Protein Serine-Threonine Kinases; imunochemie; Animals; Hybridomas; lidé; cyklin-dependentní kinasy; Neoplasms; mutace; Base Sequence